Incidence, Socio-demographic Characteristics and Predisposing Factors of Ectopic Pregnancy attended at a Private Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Ectopic pregnancy is frequently occurs among pregnant women.Objective: The purpose of the present study was to see the incidence and socio-demographic characteristics of ectopic pregnancy patients.Methodology: This cross-sectional study was carried out in the inpatient Department of Obstetrics and Gynaecology at Bangladesh Medical College Hospital, Dhaka, Bangladesh from January 2009 to December 2009 for a period of one (1) year. All clinically suspected cases of ectopic pregnancy within the reproductive age admitted in the department of Obstetrics and Gynaecology at Bangladesh Medical College Hospital, Dhaka were included in the present study. After taking detailed history with particular scrutinization of the menstrual, obstetric and contraceptive history, a thorough physical examination was performed. The ectopic pregnancy was confirmed by laboratory and imaging technique.Result: The incidence of ectopic pregnancy in BMCH was 2.16% cases.The mean age with SD of the study population was 24.0±2.87 years. The ectopic pregnancy was closely related with high parity and it had been found that para-2 was the most common which was 20(44%) cases.Pelvic infection (33.0%), past history of abortion or MR (28.0%), and history of infertility (25.0%) were constituted the main bulk of risk factors. Only 3.0% had history of tuberculosis.Conclusion: In conclusion young para 2 women with pelvic infection or past history of abortion or MR are most commonly suffering from ectopic pregnancy.Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 59-63